Images compression process in the radiological service unit as an infrastructure component in the Colombian health model - Aparicio Pico, Lilia Edith; Cardena, Julián Luciano; López Sevillano, Alexandra (TECCIENCIA, 2015)
This article depicts the process of images compression for the Discrete Cosine Transform (DCT). By being one of the most significant transformations in the area of digital image compression the DCT transforms a block of data into a new set of values. This work presents a review of images compression applied to the field of health specifically for the radiology service, where the Discrete Cosine Transform (DCT) is used as the Inverted Discrete Cosine Transform (ICDT). In this particular case, a rapid algorithm is used for DCT, which is figured out by applying the parallel arithmetic allowing the designed architecture to reach a better performance in software implementations. Firstly the different imaging modalities that are introduced into the compression system to obtain results through simulations in Matlab are included here. Subsequently, based on the results the application of radiology service is seen within the infrastructure component in the health sector and finally an analysis of production from 2011 to 2014 of hospitals is observed.